Pengaruh Pemberian Motivasi Belajar Dalam Bentuk Media Tulis Berupa Buletin Dan Poster Terhadap Aktivitas Belajar Siswa - Salim, M Barkah; Saputri, Rifka (Universitas Hamzanwadi, 2017)
From the observations in SMP Utama Wacana III Tulang Bawang Barat, the motivation of the students is very low, so the students' learning activity is low to. This problem appears when the teacher explains the teori, some students are drowsy, daydreaming, there is also chatting with his friends. This study aims to determine the effect of student learning activities with the provision of motivation in the form of written media in the form of bulletins and posters. The research method is experimental method using two classes, that is experiment class and control class. The data collecting is done by posttest only control group design. From the results of research conducted, it was found that the average learning activity that was given the motivation to use the media in the form of bulletin and poster higher than the average of learning activities that are not motivated using the media in the form of bulletins and posters with test data difference of two average obtained t -hit = 3.95 and t-daf = 1.68, showing t-hit> t-daf. So it is important if in the classroom given posters that can motivate students and if you can add with articles that can increase student motivation as well, awareness for learning increases so that student learning activities increase.